182 Highly potent fully human anti-VISTA antibodies – a new target checkpoint inhibitor against immunosuppressive myeloid cells. (10th December 2020) - Guillaudeux, Thierry; Tarcha, Eric; Bader, Robert; Dutzar, Benjamin; Eyde, Nathan; Frazier, Emily; Jurchen, David; Lance, Remington; Loomis, Cristina; Lustig, Kurt; Ovechkina, Yulia; Peckham, David; et al.
Abstract : Background: V-domain Immunoglobulin Suppressor of T cell Activation (VISTA/PD-1H) is a B7 family ligand expressed on circulating and intratumoural myeloid cells as well as Treg and NK cells. It has been shown to inhibit T cell responses in vitro and in preclinical models. In patients, VISTA is also a potential mediator of resistance to anti-CTLA-4 and anti-PD1 therapies and therefore is a valuable new target for cancer immunotherapy. Methods: Kineta has analyzed 107 fully human ScFv antibodies directed against VISTA. Results: Our lead candidates exhibit high potencies in the subnanomolar range and are also characterized by a long kDis. They specifically target human and cynomolgus monkey VISTA on a singular unique epitope. In a Staphylococcus Enterotoxin B T-cell activation assay, Kineta's anti-VISTA antibodies efficiently induce IFNg secretion. They also promote strong maturation of Antigen Presenting Cells with an increase of CD80 and HLA-DR surface expression as well as CXCL10 secretion. The mechanism of action is mediated in part by NK cells. We demonstrated that myeloid cells acquire a high level of VISTA expression during MDSC or M2 differentiation in vitro and that Kineta's anti-VISTA antibodies prevent the differentiation of MDSC as well as their immunosuppressive activity against T cells. Anti-VISTA antibodies mediate single-agent antitumor effects in syngeneic tumor models in wild-type mice and show enhanced activity in combination with anti-PD1 and anti-CTLA-4 treatment. Candidate anti-VISTA antibodies have also been evaluated in exploratory tolerability and PK studies in cynomolgus monkey. These studies demonstrated that multiple weekly doses of antibodies are well-tolerated with appropriate PK for lead selection and optimization. Conclusions: Our results strongly favor further characterization and continued development of selected lead antibodies for the potential treatment of colder, less immunogenic tumors. Ethics Approval: Study approved by the Institutional Animal Care and Use Committee PHS Assurance # D16-00885 and D16-00114